The scope and extent of exogenous surfactant utilization in Nigerian health care facilities: benefits of its regular use to outcome of premature babies. (17th April 2020) - Okonkwo, Ikechukwu Richard; Okolo, Angela A.
Abstract: Background: Surfactant replacement therapy (SRT) is the standard of care in developed countries. Poor access to surfactant limits its use in low resource settings. The extent of its use and the effect of its regular use on the preterm in such settings is unknown. Objective: This study assessed the extent of exogenous surfactant utilization in Nigerian tertiary care facilities and the benefits of its regular use to the preterm population. Methods: A two-phase cross-sectional study design evaluated the response from a respondent administered structured questionnaire addressed to health care providers from 54 centers and a targeted assessment of the outcome of the regular use of exogenous surfactant in a tertiary care facility from January 2014 to December 2016. Results: SRT was available in 16.7% of 54 units evaluated nationally; three (33.3%) were located in south-south and south-west respectively, 2 (22.2%) in southeast and one (11.1%) in north-central regions of the country. Twenty-two percent of the units were private centers, 77.8% were public tertiary care facilities. Four (44.4%) units provide SRT as the standard of care while five (66.6%) provide the service on request. One thousand one hundred twenty babies were admitted to the audited tertiary facility with 550 (49%) as preterms. Only 2.72% received surfactant replacement therapy. Sixty-six percent of recipients survived whilst 33.3% died. Respiratory support positively enhanced outcome in recipients of surfactant therapy. Conclusion: There is a limited use of surfactant nationally. Its use seemed to have improved survival.